SAT0326 Validity of Ultrasound in the Assessment of Pulmonary Fibrosis in Systemic Sclerosis: Correlation with High Resolution Computed Tomography, Pulmonary Function Test and Histological Findings. (10th June 2014) - Gutierrez, M.; Pineda, C.; Navarro, C.; Salaffi, F.; Hernandez, C.; Ventura, L.; Carotti, M.; Grassi, W.
Abstract : Background: Pulmonary fibrosis (PF) is a frequent manifestation in systemic sclerosis (SSc). Currently, high resolution computer tomography (HRCT) is the most common imaging technique used in the assessment of PF; however, its use involves high dose of ionising radiation. Recently the potential role of ultrasound (US) B-lines for the assessment of PF has been proposed (1-2). However studies aimed to test its validity are still lacking. Objectives: To investigate the validity, reliability and feasibility of the US in the assessment of PF by a correlation with HRCT, pulmonary function test (PFT) and histological findings in patients with SSc. Methods: Seventy-two patients with diagnosis of SSc were included. Each patient underwent clinical examination, PFT, chest HRCT and US. In 22 patients a histological assessment of the lung was assessed. HRCT and lung US were performed by experienced radiologist and rheumatologist respectively. A second rheumatologist carried out US examinations to assess the inter-observer agreement. In each patient a simplified US B-lines assessment as previously proposed (3) was performed. It included bilaterally 14 lung intercostal spaces (LIS): for the anterior chest: 2nd LIS along the para-sternal lines, 4th LIS along the mid-clavear, anterior axillary and mid-axillary lines. For the posterior chest: 8th LIS along the paravertebral, sub-scapular and posterior axillary lines. The following semiquantitative scoring was adopted was [0 = normal, (<5 B-lines); 1 = mild (from 6-15 B-lines); 2 = moderate (from 16 to 30 B-lines) and 3 = marked (>30 B-lines). For criterion validity, the histological assessment was considered the gold standard. Feasibility and intra-observer reliability was also investigated. Results: A total of 1008 LIS in 72 patients were assessed. A significant linear correlation between US B-lines, HRCT score (p<0.001) and histological assessment (p<0.0001) was found. Moreover, a positive correlation was obtained between US B-lines assessments and values of DLco (p=0.014). Both kappa values and overall agreement percentages of inter-observer showed an excellent agreement (0.943 and 93% respectively). The mean time spent for each US examination (including the 14 LIS), was 8.9 ±SD 1.4, range 6-12 minutes. Conclusions: Our preliminary results support the validity and reliability of US as additional imaging method in the assessment of PF in patients with SSc. References: Gargani L, et al. Ultrasound lung comets in sistemic sclerosis: a chest sonography hallmark of pulmonary interstitial fibrosis. Rheumatology 2009;48:1382-7. Barskova T, et al. Lung ultrasound for the screening of interstitial lung disease in very early systemic sclerosis Ann Rheum Dis 2013;72:390-5. Gutierrez M, et al. Utility of a simplified ultrasound assessment to assess interstitial pulmonary fibrosis in connective tissue disorders-preliminary results. Arthritis Res Ther 2011:18;13:R134. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5683